A Pastor's Toolbox 2 : More Management Skills for Parish Leadership - Holmes, Paul A. (Book collections on Project MUSE., 2017)
"The remarkable success of the book A Pastor's Toolbox: Management Skills for Parish Leadership has demonstrated that the demands of time and financial challenges continue to impact the work of today's parish leaders. The need has become even greater for practical tools to assist in the many aspects of temporal administration, leadership, and church management. This follow-up volume provides all new information, insights, and practical tools that pastors need to handle the complexities of parish management in the twenty-first century. Sixteen contributors from across the country deliver key content that focuses on promoting excellence and best practices in the areas of management, finances, communications, and human resources development. A Pastor's Toolbox 2 provides: leadership tools for the pastor and his team;help for working with the parish's pastoral and finance council;intercultural competence and complex pastoring situations;suggestions for time management and effective meetings;human resources, change management, and canon law;tools for parish stewardship, communications, and Catholic schools.The book is an outgrowth of the Toolbox for Pastoral Management, a nationally recognized joint project of Leadership Roundtable and Seton Hall University."--Publisher.